Transformation of The Regional Economic Structure of West Nusa Tenggara Province: Sectoral GRDP Analysis 2015-2024 - Rizwan Aldi; Baiq Ismiwati; M. Jumaedi (Tinta Emas Publisher, 2026)
This study identifies the direction, magnitude, and temporal reversals of structural change in West Nusa Tenggara (NTB), a resource-dependent Indonesian province. Official real gross regional domestic product (GRDP) for 17 industries in 2015–2024 is reconstructed into transparent primary, secondary, and tertiary groups. The analysis combines annual growth, contribution shifts, compound growth, volatility, end-point and chained Structural Change Indices (SCI), and concentration measures. All underlying values are disclosed, and an internal-consistency audit is applied to the draft’s reported location quotients. Real GRDP increased from IDR 89.338 trillion to IDR 109.415 trillion (2.28% compound annual growth). The primary share declined by 7.56 percentage points, the tertiary share increased by 6.04 points, and the secondary share rose by only 1.52 points. Mining alone explains a 7.35-point loss, whereas trade (+2.69 points) and construction (+1.28 points) were the largest gainers. Tertiary output grew 3.90% annually and secondary output 3.54%, compared with 0.31% for the primary group. Yet the cumulative annual three-group SCI (19.17 points) was 2.54 times the net 2015–2024 SCI (7.56), showing that end-point comparisons conceal substantial shock-driven reversals. NTB experienced service-led diversification rather than deep industrialization. The result supports a policy shift from interpreting sector shares as an automatic productivity transition toward strengthening tradable services, manufacturing linkages, skills, and resilience to mining cycles.